Українські шерифи - Bondarchuk, Roman (Ukraine ; Germany ; Latvia : Taskovski Films, 2015)
Viktor and Volodya were appointed local sheriffs by the mayor in the town of Stara Zburyevka, Ukraine. Their duty is to mend the quarrels and problems of the community in a village with no regular police force. Driving in their yellow Lada, flying its own little Ukrainian flag, they travel from incident to incident, calming an angry neighbor, investigating the discovery of a body, struggling to unfold a stroller and attempting to re-integrate Vova, the freeloader who eats other people’s dogs but actually longs for a normal existence. The seasons pass until political developments reach the village by way of the TV screen, sowing separatist discord. Around the time of the celebrations for the country’s Independence Day, the men of the village are drafted into the army. 'Ukrainian Sheriffs' offers insight into the everyday life of a Ukrainian village observed with dry humor and a great eye for detail.
Verzio Film Festival Submission
Keywords: Documentary films